2001
DOI: 10.2165/00063030-200115070-00005
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin: A Review of its Clinical Properties in the Management of Hepatic Disorders

Abstract: The antioxidant properties of silymarin (a mixture of at least 4 closely related flavonolignans, 60 to 70% of which is a mixture of 2 diastereomers of silybin) have been demonstrated in vitro and in animal and human studies. However, studies evaluating relevant health outcomes associated with these properties are lacking. Although silymarin has low oral absorption, oral dosages of 420 mg/day have shown some therapeutic potential, with good tolerability, in the treatment of alcoholic cirrhosis. Moreover, silybi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
275
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 412 publications
(291 citation statements)
references
References 32 publications
10
275
0
6
Order By: Relevance
“…Similar or possibly identical transport mechanism inhibited by silibinin was described for amanitin (Wellington and Jarvis, 2001). Therefore, silymarin is able to reduce the cellular absorption of noxious xenobiotics other than mushroom poisons, thereby exerting cell-protection.…”
Section: Phalloidin (A Bicyclic Heptapeptide) and Antamanide (A Monocsupporting
confidence: 66%
“…Similar or possibly identical transport mechanism inhibited by silibinin was described for amanitin (Wellington and Jarvis, 2001). Therefore, silymarin is able to reduce the cellular absorption of noxious xenobiotics other than mushroom poisons, thereby exerting cell-protection.…”
Section: Phalloidin (A Bicyclic Heptapeptide) and Antamanide (A Monocsupporting
confidence: 66%
“…Silymarin possesses hepatoprotective properties and has been widely used for decades to treat patients with liver disease (8). Recent studies have shown that silibinin and silymarin inhibits growth of many cancers including breast, lung, colon, pancreas, and prostate cancer cells (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…seeds, and is widely known for its hepatoprotective and cancer chemopreventive action (Wellington and Jarvis, 2001;Agarwal, 2002, 2006;Deep et al, 2006). Recently, we have isolated and purified from silymarin seven distinct flavonolignans namely silybin A, silybin B, isosilybin A, isosilybin B, silydianin, silychristin, isosilychristin and one flavonoid taxifolin ; and assessed their biological effects on many antiproliferative end points in human PCA cell lines (Davis-Searles et al, 2005).…”
Section: Introductionmentioning
confidence: 99%